How Moral Value Commitments Shape Responses to Political Civility and Incivility. Issue 4 (July 2021) - Walter, Annemarie; Lipsitz, Keena
Citizen exposure to political incivility is increasing. Studies have found heterogeneous responses to incivility, but we know little about what drives this variation. This study investigates whether emotional responses to both civility and incivility are driven by moral value commitments. Drawing on Moral Foundations Theory, we argue that incivility should pose more of a threat to people who embrace an individualizing system of moral regulation than a binding system. To test this, we conduct a 3 × 3 between-subjects survey-embedded vignette experiment with a representative sample of 1, 789 U.S. respondents. The vignettes describe interactions between two candidates in a debate. The findings show that respondents clearly distinguish between civil, neutral, and uncivil debate and that these conditions yield distinct emotional responses. Moreover, we show "individualizers" have a stronger emotional response to incivility than "binders." Responses to civility, however, appear to be unaffected by moral value commitments.